Understanding oneself for a better future: reproductive health awareness for adolescent boys and girls - Dewi Nurhanifah; Septia Maharani Putri (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2025)
Adolescence is a critical period marked by significant physical, emotional, and psychological changes, especially related to reproductive health. However, the lack of access to accurate and age-appropriate information often leads to misunderstandings and risky behaviors. This community service program aims to increase awareness and understanding of reproductive health among adolescent boys and girls. The activity was carried out through interactive health education sessions, group discussions, and question-and-answer segments involving students from junior and senior high schools in Banjarmasin, South Kalimantan. The topics included puberty, reproductive system anatomy, personal hygiene, prevention of sexually transmitted infections (STIs), and the importance of making informed and responsible decisions. The results showed increased knowledge and positive attitude shifts toward reproductive health among participants, as assessed through pre- and post-activity questionnaires. This program highlights the importance of early and inclusive reproductive health education to support the development of healthy, confident, and responsible young individuals.